Selectivity of Some Herbicides to Cocksfoot (Dactylis glomerata L.), Grown for Seed Production - Dimitrova, Tsvetanka (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
The study was conducted to determine selectivity of some herbicides to cocksfoot (Dactylis glomerata L.), and their influence on the seed production, during the years 2008-2010. The trial was set on the experimental field of the Institute of Forage Crops – Pleven, on slightly leached chernozem. As a result of the research the following was found: herbicides Arat (500 g/l dicamba + 250 g/l tritosulfuron) at the dose of 100 ml/ha, Korida 75 VDG (750 g/kg tribenuron-methyl) – 15 g/ha and Cambio SL (320 g/l bentazon + 90 g/l dicamba) – 1250 ml/ha and Grasp 25SK (250 g/l tralkoxyidim) + Atplus at rate of 1000 + 1000 ml/ha had high selectivity to cocksfoot, applied at 2-4 leaf stage during establishing year of the stand, and until the stage of the beginning of shooting up in seed production year. Herbicide Topik 080EK (80 g/l clodinofop – propargyl + antidote) at rate of 300 ml/ha, showed phytotoxic effect to D. glomerata and caused the reduction of seed and dry biomass productivity.